Digital exclusion as a potential cause of inequalities in access to care: a survey in people with inflammatory rheumatic diseases. Issue 1 (6th January 2023) - Hider, Samantha; Muller, Sara; Gray, Lauren; Manning, Fay; Brooks, Mike; Heining, Dominic; Menon, Ajit; Packham, Jonathan; Raghuvanshi, Subhra; Roddy, Edward; Ryan, Sarah; Scott, Ian; et al.
Abstract: Objectives: COVID-19 led to rapid uptake of digital health care. We sought to examine digital access, health and digital literacy, and impact on confidence and satisfaction with remote consultations in people with inflammatory rheumatic diseases (IRDs). Methods: People with IRDs ( n = 2024) were identified from their electronic health record and invited to participate in a cross-sectional survey, using short message service (SMS) and postal approaches. Data were collected on demographics, self-reported diagnosis, access to and use of internet-enabled devices, health and digital literacy, together with confidence and satisfaction with remote consultations. Ethical approval was obtained (Ref 21/PR/0867). Results: Six hundred and thirty-nine (639) people completed the survey [mean (s .d .) age 64.5 (13.1) years, 384 (60.1%) female]. Two hundred and eighty-seven (44.9%) completed it online. One hundred and twenty-six (19.7%) people reported not having access to an internet-enabled device. Ninety-three (14.6%) reported never accessing the internet; this proportion was highest (23%) in people with RA. One hundred and seventeen (18%) reported limited health literacy. Even in those reporting internet use, digital literacy was only moderate. People with limited health or digital literacy or without internet access were less likely to report confidence or satisfaction with remote consultations. Conclusion: Limited health and digital literacy, lack of digital access and low reported internet use were common, especially in older people with RA. People with limited health literacy or limited digital access reported lower confidence and satisfaction with remote consultations. Digital implementation roll-out needs to take account of people requiring extra support to enable them to access care digitally or risks exacerbating health inequalities. Lay Summary: What does this mean for patients? The COVID-19 pandemic led to rapid changes in how health care was delivered and a shift to remote consultations. Many of these changes needed access to the internet (known as digital access) and confidence in using the internet (called digital literacy). To study the impact of digital access and literacy in people with inflammatory rheumatic diseases (such as RA) we asked people (by post or SMS text) to complete a survey. Six hundred and thirty-nine people responded. The average age was 64.5 years, and 60.1% of people were female. Almost 20% of people reported not having access to an internet-enabled device. Ninety-three (14.6% of people) reported never accessing the internet; this was highest (23%) in people with RA. One hundred and seventeen (18%) had limited health literacy. Even in those reporting internet use, digital literacy was only moderate. People with limited health or digital literacy or without internet access were less likely to report that they were confident or satisfied with remote consultations. Roll-out of digital innovations needs to take account of people who might need extra support to access care digitally.